JURIDICAL ANALYSIS OF SUPERVISION OF QUALITY SYSTEM IMPLEMENTATION IN FULFILLMENT OF EXPORT REQUIREMENTS FOR FISHERIES PRODUCTS TO REALIZE LEGAL PROTECTION TO THE COMMUNITY: RESEARCH STUDY AT THE OFFICE OF THE FISH QUARANTINE CENTER, QUALITY CONTROL AND SAFETY OF FISHERY PRODUCTS TANJUNGPINANG - Arrofik, Arrofik; Fadlan, Fadlan; Parroha Patar Siadari, Lagat (RADJA PUBLIKA, 2022)
The construction of the journal topics mentioned above are: